A comparative analysis of immunomodulatory genes in two clonal subpopulations of CD90+ amniocytes isolated from human amniotic fluid. (November 2020) - Hoseini, Seyed Mehdi; Sheikhha, Mohammad Hasan; Kalantar, Seyed Mehdi; Matin, Maryam M.; Aflatoonian, Behrouz; Bahrami, Ahmad Reza; Zarein, Fateme; Rahmani, Saeede; Montazeri, Fateme
Abstract: Object: Immunosuppressive and immunomodulatory activity of mesenchymal stem cells derived from different sources, such as placental membranes, umbilical cord, and amniotic fluid has been proved. The heterogeneous nature of human amniocytes have been confirmed due to different clonal subpopulations found in amniotic fluid. The aim of this study was to investigate a 17-gene panel of immunomodulatory markers in two clonal subpopulations of CD90 + amniocytes, divided based on morphology into epithelioid and fibroblastoid cells. Method: Semi-quantitative RT-PCR was used to study the expression of the chosen genes. Flow cytometry analysis confirmed the non-hematopoietic mesenchymal origin of isolated cells, based on lacking the hematopoietic marker of CD31, and the presence of mesenchymal marker of CD90 (both on more than 90% of cells). Results: Our results showed that besides growth characteristics, the two cell groups were different in expressional profile, so that, fibroblastoid clones displayed higher level of immunosuppression genes as well as mesenchymal surface marker of CD90 compared to epithelioid ones. Our previous investigation on these clones showed that epithelioid cells have a more potential to express the pluripotency genes. It seems there is an inverse relationship between genes associated with immunosuppression and pluripotency. Conclusion: Although many reports have been published regarding the immunosuppressive properties of fetal stem cells, but few studies to date have explained whether the stemness state of human amniocytes may affect their immunosuppressive potential. Further study on amniocytes, which often has self-renewal ability and high immunomodulatory potential, can help to understand the details of this relationship. Highlights: Immunosuppressive and immunomodulatory activities is one of the important characteristics essentially needed for using cells in regenerative medicine and tissue engineering. Investigating gene panel of immunomodulatory markers in subpopulations of CD90 + amniocytes. It seems there is an inverse relationship between genes associated with immunosuppression and pluripotency. Few studies to date have explained whether the stemness state of human amniocytes may affect their immunosuppressive potential. Further study of such relationships, particularly in amniocytes, which often has self-renewal ability and high immunomodulatory potential, can play an important role in understanding the basic mechanism of action of these two processes.